2022
DOI: 10.1039/d1fo04404d
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of Siberian onions against toxin-induced liver dysfunction: an insight into health-promoting effects

Abstract: Siberian onion (SO) is a delicious wild vegetable. Its taste is most unique, not only like scallions, but also like leeks or garlic. It also has a traditional medicinal value...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…By decreasing oxidative stress, onion and apple supplementations may help preventing the proinflammatory activation observed in OC vessels. Interestingly, and in line with the present findings, Jiang et al (2022) [ 79 ] recently reported that Siberian onion reduced the positive expressions of α-smooth muscle actin and NLRP3 by inhibiting signal transducer and activator of transcription 3 phosphorylation in activated hepatic stellate cells. Moreover, a study by Guo et al (2013) [ 128 ] concluded that quercetin and quercetin-3- O -glucuronide inhibited ROS-associated inflammation by blocking IKKβ/NF-κB activation and effectively facilitated insulin signaling transduction along insulin receptor substrate-1/Akt/eNOS pathway in the endothelium.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By decreasing oxidative stress, onion and apple supplementations may help preventing the proinflammatory activation observed in OC vessels. Interestingly, and in line with the present findings, Jiang et al (2022) [ 79 ] recently reported that Siberian onion reduced the positive expressions of α-smooth muscle actin and NLRP3 by inhibiting signal transducer and activator of transcription 3 phosphorylation in activated hepatic stellate cells. Moreover, a study by Guo et al (2013) [ 128 ] concluded that quercetin and quercetin-3- O -glucuronide inhibited ROS-associated inflammation by blocking IKKβ/NF-κB activation and effectively facilitated insulin signaling transduction along insulin receptor substrate-1/Akt/eNOS pathway in the endothelium.…”
Section: Resultssupporting
confidence: 91%
“…An early study shows that increased TIMP-1 levels are a risk factor for mortality among congestive heart failure patients [ 78 ]. Recently, Jiang et al (2022) [ 79 ] found that Siberian onions decreased serum transaminase levels and oxidative stress, and regulated the balance of the extracellular matrix in CCl4-induced mice, including α-smooth muscle actin (α-SMA), type I collagen, and TIMP-1, suggesting that Siberian onions reduced the release of inflammatory factors and regulated apoptosis-associated proteins, which is related to the inhibition of signal transducer and activator of transcription 3 (STAT3) phosphorylation. Additionally, considering that TIMP-1 is an inhibitor of MMP-1 in tissue and the amount of type I collagen is tightly regulated by balance between MMP-1 and TIMP-1, Cho et al (2010) [ 80 ] demonstrated that onion extract and quercetin play a role in the antifibrotic effect and promotion of wound healing in skin through up-regulation of MMP-1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Liver fibrosis means that the increase of fibrous tissue in liver tissue was caused by inflammatory stimulation. On the other hand, the sustained inflammatory response exacerbates the degree and progression of liver fibrosis. , Our findings showed that RK had the potential to reduce the levels of inflammatory cytokines in mice induced with TAA or in activated HSCs. In particular, RK could modulate the inflammatory factors of activated HSCs cultured with the supernatant of LPS-primed THP-1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is noteworthy that activated CASP3 also plays a key role in the cleavage of PARP, another pivotal enzyme in the process of apoptosis. PARP, when cleaved by CASP3, loses its ability to repair DNA and maintain cell survival, thereby pushing the cell toward apoptosis [ 50 , 51 ]. Additionally, the tumor suppressor gene Tp53 acts as a proapoptotic factor and is triggered in response to cellular stresses, including oxidative stress [ 45 ].…”
Section: Discussionmentioning
confidence: 99%